2019
DOI: 10.3390/ijms20215440
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Rapid Glutathionylation of Ribonuclease: Is This the Real Incipit of Its Oxidative Folding?

Abstract: Many details of oxidative folding of proteins remain obscure, in particular, the role of oxidized glutathione (GSSG). This study reveals some unknown aspects. When a reduced ribonuclease A refolds in the presence of GSSG, most of its eight cysteines accomplish a very fast glutathionylation. In particular, one single cysteine, identified as Cys95 by mass spectrometry, displays 3600 times higher reactivity when compared with an unperturbed protein cysteine. Furthermore, the other five cysteines show 40–50 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…By examining the reaction of the reduced molten globule-like structures of the four tested proteins with oxidized glutathione (GSSG), we found that a single specific cysteine in each protein displays thousands-times higher reactivity than an unperturbed protein cysteine (Table 1). This phenomenon has been observed in rBSA, rLyz, rRNase and rChTg, for Cys75, Cys94, Cys95 and Cys1, respectively [13][14][15][16]. This hyper-reactivity is specific for GSSG, because a normal reactivity has been found toward other natural disulfides like cystine and cystamine (see Table 1).…”
Section: Productive Transient Complexmentioning
confidence: 71%
See 4 more Smart Citations
“…By examining the reaction of the reduced molten globule-like structures of the four tested proteins with oxidized glutathione (GSSG), we found that a single specific cysteine in each protein displays thousands-times higher reactivity than an unperturbed protein cysteine (Table 1). This phenomenon has been observed in rBSA, rLyz, rRNase and rChTg, for Cys75, Cys94, Cys95 and Cys1, respectively [13][14][15][16]. This hyper-reactivity is specific for GSSG, because a normal reactivity has been found toward other natural disulfides like cystine and cystamine (see Table 1).…”
Section: Productive Transient Complexmentioning
confidence: 71%
“…This phenomenon is mainly due to a productive transient protein-GSSG complex, as proven by fluorescence and kinetic experiments which also defined the dissociation constants of this interaction (K D = 0.3 mM for rLyz, K D = 0.12 mM for rRNase and K D = 1.5 mM for rChTg) [13][14][15][16]. In other words, a specific region of the molten globule-like conformations of these proteins resembled an enzyme active site which was able to bind productively with GSSG in order to react with a selected cysteine.…”
Section: Productive Transient Complexmentioning
confidence: 78%
See 3 more Smart Citations